Ecological Distribution of Natural Fodder Grasses in Western Rajasthan - Prakash, Mahendra; Nanda, P. C. (Indian Forester, 1961)
Climate primarily controls the vegetation of a region. It is the semi-arid to arid climate of the Western Rajasthan which is responsible for providing congenial environment for the growth of some good fodder grasses. The distribution of some of the characteristic natural fodder grasses of this tract is basically controlled by effective precipitation, topography and soil conditions. Based upon these factors, the Western Rajasthan can be divided into three eco-systems and one sub-eco-system. (i) Rugged hilly projections. (i)a Folds of hillocks and stabilised sand dunes. (ii) Sandy plains with dunes and shifting sands, and (iii) Alkaline and Saline soils. Each of these systems is governed by the biotic, climatic, edaphic and physiographic factors. The severity of these factors is variously reflected in the formation of differential vegetation types, particularly the grassland communities. These eco-systems mainly should have the following species for optimum production from grasslands. Eco-system.(i) Sehima nervosum, Eremopogon foveolatus, Heteropogon contortus. Eco-system (i)a Dichanthium annulatum. Eco-system (ii) Elyonurus hirsutus, Cenchrus ciliaris, Cenchrus setigerus, Cenchrus prieuri. Eco-system (iii) Cenchrus ciliaris, Cenchrus setigerus, Cenchrus prieuri and Sporobolus arabicus. Each eco-system supports a characteristic assemblage of grasses which not only conserve the habitat characters as related to soil, but also produce the maximum possible fodder as determined by soil-climate complex. Thus the areas under each eco-system should be so managed that proper environments necessary for each assemblage of grass species to establish and improve are maintained. This can be done by adopting suitable grazing practices, soil working and other engineering devices for soil and moisture conservation, water spreading and agronomic practices.